2017
DOI: 10.3389/fmed.2017.00142
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Venous Thromboembolism: A Practical Review Beyond Low-Molecular-Weight Heparins

Abstract: Patients with cancer are at significantly higher risk of developing, and dying from, venous thromboembolism (VTE). The CLOT trial demonstrated superiority of low-molecular-weight heparins (LMWH) over warfarin for recurrent VTE and established LMWH as the standard of care for cancer-associated VTE. However, with patients living longer with metastatic cancer, long-term injections are associated with significant cost and injection fatigue. Direct oral anticoagulants (DOACs) are an attractive alternative for treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…6 Ascribed to its convenient use, some clinicians prefer to prescribe direct oral anticoagulants (DOACs) for treating cancer-associated VTE. 7 There are following 2 types of DOACs: direct factor Xa (rivaroxaban, edoxaban, and apixaban) and direct thrombin inhibitor (dabigatran). 8 Currents guidelines for the treatment of VTE have listed DOACs as one of the standard therapies in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…6 Ascribed to its convenient use, some clinicians prefer to prescribe direct oral anticoagulants (DOACs) for treating cancer-associated VTE. 7 There are following 2 types of DOACs: direct factor Xa (rivaroxaban, edoxaban, and apixaban) and direct thrombin inhibitor (dabigatran). 8 Currents guidelines for the treatment of VTE have listed DOACs as one of the standard therapies in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In a 2017 prospective cohort study of 200 patients by Mantha et al, rivaroxaban was identified as safe and effective for cancer‐associated thrombosis, with 4.4% VTE recurrence and 2.2% major bleeding . These findings are lower than the reported values of 7% to 9% and 6% to 7%, respectively, for LMWH . Equivalent findings were seen in subsequent prospective randomized trials comparing DOACs with enoxaparin and warfarin .…”
Section: Pancreatic Cancer Disease‐related Complications and Managementmentioning
confidence: 90%
“…96 These findings are lower than the reported values of 7% to 9% and 6% to Cancer November 15, 2019 7%, respectively, for LMWH. 97,98 Equivalent findings were seen in subsequent prospective randomized trials comparing DOACs with enoxaparin 99,100 and warfarin. 101 However, in similar studies between DOACs and dalteparin, DOACs were noninferior but had an increased risk of bleeding.…”
Section: Pancreatic Cancer-related Symptom Managementmentioning
confidence: 96%
“…Treatment of choice is the group of Low Molecular Weight Heparins (LMWH) undoubtfully [22]. Long-term treatment with LMWH is considered safer and more efficacious than standard Vitamin K Antagonists (VKA) therapy, based on the results from the CLOT and CATCH [23,24].…”
Section: Which Treatment and In What Dosing?mentioning
confidence: 99%
“…Rivaroxaban, apixaban and edoxaban as well as the direct thrombin inhibitor dabigatran, (NOACs) may offer a precious therapeutic alternative to LMWH in special subgroups of cancer patients, albeit until now no clinical trial has presented a head-to-head comparison of NOACs vs LMWH in cancer patients with acute VTE [21,22].…”
Section: Which Treatment and In What Dosing?mentioning
confidence: 99%